Electrodeposited Cobalt‐Phosphorous‐Derived Films as Competent Bifunctional Catalysts for Overall Water Splitting1. (20th April 2015) - Jiang, Nan; You, Bo; Sheng, Meili; Sun, Yujie
Abstract One of the challenges to realize large‐scale water splitting is the lack of active and low‐cost electrocatalysts for its two half reactions: H2 and O2 evolution reactions (HER and OER). Herein, we report that cobalt‐phosphorous‐derived films (Co‐P) can act as bifunctional catalysts for overall water splitting. The as‐prepared Co‐P films exhibited remarkable catalytic performance for both HER and OER in alkaline media, with a current density of 10 mA cm−2 at overpotentials of −94 mV for HER and 345 mV for OER and Tafel slopes of 42 and 47 mV/dec, respectively. They can be employed as catalysts on both anode and cathode for overall water splitting with 100 % Faradaic efficiency, rivalling the integrated performance of Pt and IrO2. The major composition of the as‐prepared and post‐HER films are metallic cobalt and cobalt phosphide, which partially evolved to cobalt oxide during OER.